POLITICAL STRATEGY OF MARKETING MIX OF PUBLIC DECISION TO CHOOSE PROSPECTIVE CANDIDATES MAYOR BANDAR LAMPUNG - Novita Sari; Jefri Ardi; Adi Kurniawan; Cindya Vitarani (Proceeding International Conference on Information Technology and Business, 2019)
The purpose of this study is to scrutinize the effect of the political marketing mix on the voters' decision. The concept of political marketing mix ie product, promotion, price and place were employed in this study. The method using mixed methods research is a research method by combining two research methods at the same time, qualitative and quantitative in a research activity, so that more of comprehensive, valid, reliable, and objective of data will be Obtained. Target respondents were Lampung city community who Voted for the 2020 Mayor election at Bandarlampung. With a sample of 400 responsiveness.Keywords: Political Marketing, Marketing Mix, the voters' decision.